2022
DOI: 10.1021/acs.macromol.2c01515
|View full text |Cite
|
Sign up to set email alerts
|

Anionic Self-alternating Polymerization of 1-(4-Vinylphenyl)-1-phenylethylene

Abstract: A new AB-type difunctional monomer, 1-(4-vinylphenyl)-1-phenylethylene (1), was subjected to anionic polymerization using sec-butyllithium (s-BuLi), diphenylmethyllithium (Ph2CHLi), and diphenylmethylpotassium (Ph2CHK) in tetrahydrofuran at 0 °C. Soluble poly­(1)­s with predicted molecular weights and relatively narrow molecular weight distributions (M w/M n = 1.1–1.3) were quantitatively obtained. 1H and 13C NMR measurements revealed that two carbon–carbon double bonds in the styrene (A) and 1,1-diphenylethyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 43 publications
(72 reference statements)
0
15
0
Order By: Relevance
“…This indicates that the anionic self-alternating polymerization of ClVD is also achieved with Ph 2 CHLi. In a previous report, we found that counterions have negligible effect on the proposed anionic self-alternating polymerization by estimating the polymerized unit in poly­( VD ) …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This indicates that the anionic self-alternating polymerization of ClVD is also achieved with Ph 2 CHLi. In a previous report, we found that counterions have negligible effect on the proposed anionic self-alternating polymerization by estimating the polymerized unit in poly­( VD ) …”
Section: Resultsmentioning
confidence: 99%
“…Relationship between the Hammett parameter and C β chemical shifts of St (red, C βSt ) and DPE (blue, C βDPE ) frameworks and polymer yields (Table , initiator: Ph 2 CHK; at −78 °C for 72 h). The yield of poly­( VD ) was obtained from the previous result …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations